Chemopreventive Effects Of Phaleria Macrocarpa (Scheff.) Boerl Aqueous Extract On Ht29 Colorectal Cancer Cells - Khalil, Nor Azlina (2020)
The aim of the study was to assess the chemopreventive activities of PMSB crude water fruit flesh (WF) and seed (WS) extracts on human colorectal adenocarcinoma, HT29 cell line by studying the inhibitory concentration dose (IC50), looking at the morphological changes, its effect on apoptosis and cell cycle regulation as well as the proteins involved.